POTENCIAL EFEITO ANTITUMORAL DO CACAU (Theobroma cacao L.) EM LIPOSSOMAS FRENTE A CÉLULAS DE LEUCEMIA PROMIELOCÍTICA AGUDA (NB-4) - Ribeiro, Mariana Fernandes (2021)
Acute promyelocytic leukemia is highlighted by the fusion of the PML-RARA genes causing cellular immaturity and accelerated proliferation of promyelocytes, causing symptoms such as hemorrhagic crises. Despite the efficacy of drugs such as all-trans retinoic acid and arsenic trioxide, some patients have important adverse reactions. Studies indicate that natural products are capable of acting in a chemotherapeutic manner with no or low adverse effect. In this context, cocoa (Theobroma cacao L.) was investigated for containing a chemical matrix rich in polyphenols and methylxanthines, capable of acting in an anti-tumor, anti- inflammatory and antioxidant manner. Due to its low bioavailability, an outbreak of nanotechnology as an efficient alternative to provide and improve the solubility of compounds through liposomal nanocarriers. The present study aims to evaluate the potential antitumor effect of liposomes containing cocoa against acute promyelocytic leukemia cells. Liposomes containing cocoa powder were collected in procedures of 1, 2 and 3 mg / mL-1 by the reverse phase evaporation method. The formulations produced were stored at room temperature (RT) (24 ± 2 ºC), refrigeration (RE) (4 ± 2 ºC) and climatic chamber (CC) (40 ºC 75% relative humidity) for evaluation during 90-day stability. Average particle diameter, polydispersity index, pH, catechin and methylxanthine content, encapsulation efficiency and organoleptic characteristics were adopted. Subsequently, a possible cytotoxic effect of liposomes and free cocoa was evaluated on fibroblast cell line (HFF-1) and acute promyelocytic leukemia (NB-4) from cell viability and levels of reactive oxygen species. Liposomes containing 1 mg / mL- 'remained stable for 30 days when stored in refrigeration, particle volume of 216.8 nm, polydispersity index of 0.375, zeta potential of -7.27 mV, pH 5.55 and content 3.23% theobromine, 0.74% theophylline, 1.11% catechin, 1.59% caffeine. In in vitro tests, the HFF-1 strain did not show reduced cell viability and proliferation in a reduced way. Still, it was found that the NB-4 cells dissipated cell proliferation and increased levels of reactive oxygen species within 72 hours in both treatments. It is concluded that liposomes are promising nanostructures for the encapsulation of catechins and methylxanthines as the compounds present in cocoa, in addition to having a potential carginogenic effect in acute promyelocytic leukemia cells.